PROGRAM INTERVENSI PENGEMBANGAN KECAKAPAN BERBICARA ANAK DOWN SYNDROME - Kurniawati, Lely; Alimin, Zaenal; Asri, Pudji (Universitas Pendidikan Indonesia, 2015)
Speech and language is an initial capability to be owned subsidiaries as capital to be able to interact and communicate. Intervention is given to those who experience barriers to development including speech development of language in children with Down syndrome. This study aims to formulate intervention programs in accordance with the development and needs of children with Down syndrome. This study to determine the speech development in children with down syndrome and the efforts that have been undertaken to help develop their speaking skills. This study used mixed methods with sequential exploratory design, which is a design study that combines qualitative and quantitative research gradually. Results from this study showed that the ability to speak the child is still limited to the pronunciation of the word without any specialhandling. The program consists of interventions designed aspects of understanding of the vocabulary, syntax and schematically drawn based on the child's development. The results of the implementation of this program showed improvement in the children speak a few words. This program can be implemented in teaching and learning in the classroom. More attention in children can help children with Down syndrome improve speaking ability.Keywords: intervention program, speech intelligibility, down syndrome, mixed methods